PENERAPAN PENDEKATAN INKUIRI UNTUK MENINGKATKAN KETERAMPILAN PROSES SISWA PADA PEMBELAJARAN IPA POKOK BAHASAN KONDUKTOR DAN ISOLATOR PANAS - Suansah, Suansah (Profesi Pendidikan Dasar, 2015)
This study aims to improve the skills of students through the application process inquiryapproach. The method used is Classroom Action Research (PTK), which starts from the actionplanning, action, observation, refl ection and then make plans for improvement that are used inthe next cycle. This research is conducted in two cycles. Overall the action is performed in thefi rst cycle and the second directed to bring science process skills (KPS) students, especially inthe aspect of observation. The analysis showed that students’ prior learning process skills arestill low with an average score of 5.40 KPS. Skills of students in the observation process afterlearning has increased very signifi cantly. In the fi rst cycle of PPP Observation of studentscategorized quite skilled with the percentage of 60 %. In the second cycle becomes skilledcategory with the percentage 86.66 %. In cycle it, an average score of KPS students pretest inposttest scores are 5.40 and 7.13. In the second cycle an average score of 7.30 KPS in pretestand posttest score are of 9.03.